1995
DOI: 10.1088/0022-3727/28/4/026
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved observation of gas-dynamic discontinuities arising during excimer laser ablation and their interpretation

Abstract: Ablation of materials (Cu is presented in this report) in air at an ambient gas pressure of 1 bar with a KrF excimer laser (3-47 J cm-2) leads to gasdynamic processes above the target surface which affect the processing result, the efficiency of the treatment and the debris in the environment of the irradiated area. These laser-induced processes have been diagnosed using fast schlieren photography and shadowgraphy. Five discontinuities have been discerned and their propagation mechanisms have been detected. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(77 citation statements)
references
References 15 publications
6
69
1
1
Order By: Relevance
“…These include pulsed laser deposition of high criticaltemperature superconductor films 1,2 , femtosecond laser micro-machining and structural modification of dielectrics 3,4 , ultrafast laser-assisted material and chemical analysis 5,6 , and ultrashort X-ray pulse generation 7,8 . However, high power, short pulse laser ablation is still largely unexplored at the fundamental level.Mechanisms underlying laser ablation processes are quite complex, most previous investigations have focused on laser ablation at relatively long (e.g., nanosecond and picosecond) time scales 9,10 . Since the femtosecond time scale is much shorter than the electron-lattice energy relaxation time, thermal equilibrium cannot be established during the time the laser interacts with a solid material.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include pulsed laser deposition of high criticaltemperature superconductor films 1,2 , femtosecond laser micro-machining and structural modification of dielectrics 3,4 , ultrafast laser-assisted material and chemical analysis 5,6 , and ultrashort X-ray pulse generation 7,8 . However, high power, short pulse laser ablation is still largely unexplored at the fundamental level.Mechanisms underlying laser ablation processes are quite complex, most previous investigations have focused on laser ablation at relatively long (e.g., nanosecond and picosecond) time scales 9,10 . Since the femtosecond time scale is much shorter than the electron-lattice energy relaxation time, thermal equilibrium cannot be established during the time the laser interacts with a solid material.…”
mentioning
confidence: 99%
“…Mechanisms underlying laser ablation processes are quite complex, most previous investigations have focused on laser ablation at relatively long (e.g., nanosecond and picosecond) time scales 9,10 . Since the femtosecond time scale is much shorter than the electron-lattice energy relaxation time, thermal equilibrium cannot be established during the time the laser interacts with a solid material.…”
mentioning
confidence: 99%
“…32 On the other hand, Callies et al have calculated surface pressure during the ablation of Cu target with 60 ns pulses. 33 The authors reported that surface pressure returns to ambient conditions soon after the end of the pulse duration, at around 100 ns. Therefore, the used gas pressure can suffice for divert the ablation plume.…”
Section: A Determination Of Stable Measurement Signal Conditionsmentioning
confidence: 99%
“…These works report spherical expanding shock waves when high energy pulses in mJ range with ns-level durations are used. Callies et al estimated the fraction of pulse energy deposited in the shockwave assuming a point explosion on metallic targets and pulse energies varying between 1.4-12 mJ and 60 ns pulses [20]. Amer et al compared the energy component in a spherical expansion to the laser energy to estimate the energy conversion efficiency, using 15 mJ and 12 ns pulses on polycrystalline boron nitride (PCBN) [24].…”
Section: Shock Wave Expansionmentioning
confidence: 99%
“…On the other hand, several techniques for monitoring ablation dynamics can be employed for a direct observation of the ablation plume and shock wave. The monitoring methods are mainly based on optical approaches such as probe beam deflection [12,13], shadowography [14][15][16][17][18][19], schlieren photography [20], interferometry [21,22] and digital holography [23][24][25][26]. The previous works in the literature have provided a better understanding of the ablation phenomenon in general.…”
Section: Introductionmentioning
confidence: 99%